2015
DOI: 10.1016/j.scitotenv.2015.01.086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of natural colonisation of cementitious materials: Effect of bioreceptivity and environmental conditions

Abstract: Incorporation of living organisms, such as photosynthetic organisms, on the structure envelope has become a priority in the area of architecture and construction due to aesthetical, economic and ecological advantages. Important research efforts are made to achieve further improvements, such as for the development of cementitious materials with an enhanced bioreceptivity to stimulate biological growth. Previously, the study of the bioreceptivity of cementitious materials has been carried out mainly under labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…The ability to exist in such an alkaline, high-salt environment is crucial for calcium carbonate-precipitating bacteria because concrete itself represents such environments [9,26]. Therefore, the three strains, Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to exist in such an alkaline, high-salt environment is crucial for calcium carbonate-precipitating bacteria because concrete itself represents such environments [9,26]. Therefore, the three strains, Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of a bacterial culture environment such as temperature and aeration can influence the types of calcium carbonate produced by CCP-capable bacteria [11,17,26]. Because all three strains were incubated under the same conditions, the different structure (shape) of the resulting precipitated crystals could be due to differences in their innate mechanisms of utilization of calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Sa values were of the same order of magnitude for CEM I, CEM III and CAC surfaces (1.10-1.62 µm) but the value was much higher for CEM I-Ox ones (5 µm) ( Table 2). Some studies have investigated the impact of mortar surface roughness on fungal colonization [17,18] and have found the Sa parameter to be between several tens of nm and several tens of µm. However, surface texture was not characterized, notably through skewness or kurtosis.…”
Section: Initial Surface Topology Of the Cement Pastesmentioning
confidence: 99%
“…Firstly, the calibration of pore size can enable water absorption and retention, reaching colonising organisms through capillary or surface-binding effects, and secondly as a means to exploit extrinsic factors for bioreceptivity through the collection of organic material and fixation of cryptogamic surface cover. Different compositions of bioreceptive cementitious materials have been explored based on Magnesium Phosphate Concrete (Manso et al, 2015) and other Ordinary Portland Concrete (OPC) mixes with the aim to create long-term carbon offset. Studies of OPC have shown that apart from altering the physico-chemical properties of materials, morphological variations explored via computational design strategies are a powerful means to reduce water run-off and increase moisture retention, extending the residence time to create zones for accelerated growth (Cruz, 2021).…”
Section: Bioreceptive Materials and Bio-integrated Designmentioning
confidence: 99%